Banking Deregulation and Growth: A Reappraisal - Iryna Stewen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper builds on a large literature that has exploited the experiment of US bank branching and inter-state banking deregulation since the 1970s as a natural laboratory that allows to study the real effects of liberalization and financial integration. Whereas most of the literature presented sizable effects of intra-state deregulation on a wide range of economic outcomes, interstate deregulation has generally been found to be much less important. Exploring the interaction between financial development, financial integration and long-term growth we suggest that it is the state-specific chronological order between inter-state banking and intra-state branching deregulations that has interesting implications for the patterns of growth and industrial structure. On the one hand, intra-state branching deregulation was especially important in states that had not yet deregulated their interstate banking regime and for the manufacturing sector. On the other hand, abolishing inter-state banking restrictions had a pronounced effect in states that integrated prior to intrastate branching deregulation and for the financial sector.
Keywords: G21; F36; O47; 330